Isolasi Dan Identifikasi Bakteri Escherichia coli, Klebsiella sp., Dan Staphylococcus aureus Pada Ambing dan Susu Kambing Peranakan Etawa - Cahyaningtyas, Dinda Eri; Gaina, Cynthia D; Tangkonda, Elisabet (Jurnal Veteriner Nusantara, 2024)
A disease that is usually found in etawa crossbreed goats is mastitis. Mastitis can be caused by Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus bacteria. This study aims to isolate and identify Escherichia coli, Klebsiella sp, and Staphylococcus aureus bacteria found in the mammary of etawa crossbreed goats and determine the level of bacterial colonization of Escherichia coli, Klebsiella Sp., and Staphylococcus aureus in the milk of etawa crossbreed goats calculated using the Total Plate Count (TPC) test. The samples used in this study were mammary swabs and milk from 6 PE goats. Isolation and identification of bacteria in the mammary were carried out by planting samples on differential and selective media, Gram staining, and biochemical tests. Calculation of bacterial colonies in PE goat milk used by TPC test. The results of this study indicated that Escherichia coli and Staphylococcus aureus were successfully isolated and identified from 6 PE goat mammary, but Klebsiella sp was only found in 1 PE goat mammary. The TPC value of PE goat milk obtained an average of 2.9x105 and it’s still below the maximum SNI standard for fresh milk, but exceeds the Thai Agricultural Standard for fresh goat's milk, its 2x105 CFU/ml.